Leptospira infections in Domestic and Wild Animal (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Leptospirosis is a worldwide-distributed, re-emerging zoonosis due to the large variety of wild and domestic animal species that can play the role of natural or accidental host. Currently, specific animal species play an important role as reservoirs for particular Leptospira serovars, although recent investigations have highlighted new host–pathogen interactions involved in Leptospira epidemiology. Furthermore, the constant modification of ecosystems and wildlife habitats and the constantly increasing number of animal species moving towards urban or peri-urban areas are increasing the possibility of direct or indirect contact between wildlife and domestic animals; furthermore, the constant modification of animal leptospirosis also causes problems for human health. The studies published in this book have evidenced and confirmed the hidden role of a large variety of animal species, domestic and wild, in leptospirosis epidemiology. They highlighted the necessity for continuous monitoring and large-scale surveillance studies to better understand this neglected and re-emerging zoonosis.